Polysaccharide‐Polyplex Nanofilm Coatings Enhance Nanoneedle‐Based Gene Delivery and Transfection Efficiency. Issue 36 (30th June 2022) - Hachim, Daniel; Zhao, Juzhi; Bhankharia, Jash; Nuñez‐Toldra, Raquel; Brito, Liliana; Seong, Hyejeong; Becce, Michele; Ouyang, Liliang; Grigsby, Christopher L.; Higgins, Stuart G.; Terracciano, Cesare M.; Stevens, Molly M.
Abstract: Non‐viral vectors represent versatile and immunologically safer alternatives for nucleic acid delivery. Nanoneedles and high‐aspect ratio nanostructures are unconventional but interesting delivery systems, in which delivery is mediated by surface interactions. Herein, nanoneedles are synergistically combined with polysaccharide‐polyplex nanofilms and enhanced transfection efficiency is observed, compared to polyplexes in suspension. Different polyplex‐polyelectrolyte nanofilm combinations are assessed and it is found that transfection efficiency is enhanced when using polysaccharide‐based polyanions, rather than being only specific for hyaluronic acid, as suggested in earlier studies. Moreover, results show that enhanced transfection is not mediated by interactions with the CD44 receptor, previously hypothesized as a major mechanism mediating enhancement via hyaluronate. In cardiac tissue, nanoneedles are shown to increase the transfection efficiency of nanofilms compared to flat substrates; while in vitro, high transfection efficiencies are observed in nanostructures where cells present large interfacing areas with the substrate. The results of this study demonstrate that surface‐mediated transfection using this system is efficient and safe, requiring amounts of nucleic acid with an order of magnitude lower than standard culture transfection. These findings expand the spectrum of possible polyelectrolyte combinations that can be used for the development of suitable non‐viral vectors for exploration in further clinical trials. Abstract : Herein, nanoneedles coated with polysaccharide‐nanofilms enhance transfection efficiency of polyplexes, using an order of magnitude lower in gene cargo, compared to existing delivery systems. This enhancement is attributed to the physicochemical properties of the anionic polysaccharides. Nanofilms enable surface‐mediated and spatially controlled gene delivery in cells and tissues, which is also applicable to microneedles, devices, and other bioengineered systems.